2019
DOI: 10.1111/jcmm.14784
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐1275 induces radiosensitization in oesophageal cancer by regulating epithelial‐to‐mesenchymal transition via Wnt/β‐catenin pathway

Abstract: Acquired radioresistance is one of the main obstacles for the anti‐tumour efficacy of radiotherapy in oesophageal cancer (EC). Recent studies have proposed microRNAs (miRNAs) as important participators in the development of radioresistance in various cancers. Here, we investigated the role of miR‐1275 in acquired radioresistance and epithelial‐mesenchymal transition (EMT) in EC. Firstly, a radioresistant cell line KYSE‐150R was established, with an interesting discovery was observed that miR‐1275 was down‐regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…miR-221-3p and miR-222-3p reduce radiosensitivity in thyroid cancer cells. It was previously reported that EMT was associated with decreased cancer sensitivity to radiation therapy (22)(23)(24)(25). Therefore, a colony formation assay was used to determine the role of miR-221-3p and miR-222-3p in radiosensitivity.…”
Section: Mir-221-3p and Mir-222-3p Regulate The Expression Levels Of P-stat3 Emt-related Markers And Nis In Thyroid Cancer Cellsmentioning
confidence: 99%
“…miR-221-3p and miR-222-3p reduce radiosensitivity in thyroid cancer cells. It was previously reported that EMT was associated with decreased cancer sensitivity to radiation therapy (22)(23)(24)(25). Therefore, a colony formation assay was used to determine the role of miR-221-3p and miR-222-3p in radiosensitivity.…”
Section: Mir-221-3p and Mir-222-3p Regulate The Expression Levels Of P-stat3 Emt-related Markers And Nis In Thyroid Cancer Cellsmentioning
confidence: 99%
“…For instance, the overexpression of miR-32-5p contributed to radioresistance by targeting Transducer of ERBB2, 1 in colorectal cancer (30). miR-1275 elevation diminished epithelialto-mesenchymal transition-induced radioresistance through Wnt/β-catenin signaling in esophageal cancer (31). Impediment of miR-365 suppressed the radiosensitivity of NSCLC via promoting cell division cycle 25A (32).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identi ed that miR-1275 participate in and regulates the genesis and progression of tumors [25][26][27][28][29]. Xie et.al reported that in glioblastoma miR-1275 was involved in the modulation of a series of genes related to tumor progression, CSCs maintenance, cell maturation and differentiation, which provided a new therapeutic target for differentiation induction therapy [25].…”
Section: Discussionmentioning
confidence: 99%